ANALISIS PENERAPAN METODE MENGAJAR OLEH GURU SOSIOLOGI - Hajira, Hajira; Budjang, Gusti; Salim, Izhar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract:The title of this thesis is "Analysis of Application of Teaching Methods by Sociology Teachers In Class X IPS 1 In SMA Muhammadiyah 1 Pontianak". The problem of this research is "How Application of Teaching Method By Sociology Teacher In Class X IPS 1 in SMA Muhammadiyah 1 Pontianak? "This research is done by descriptive research method using qualitative form. The research technique used is the technique of observation and documentation techniques with data collection tool in the form of observation and interview. The results showed that (1) what teaching method used by the teacher of sociology.From the results of research on the sociology teacher class X IPS 1 SMA Muhammadiyah 1 Pontianak, while the teaching process of teachers using teaching methods are not balanced which means that teachers in applying teaching methods using only lecture and question and answer methods only so as not to adjust to the Plan of Implementation of Learning (2) How Implementation of teaching methods by teachers of sociology on students. Implementation of teaching method by teacher of sociology at student of class X IPS 1 SMA Muhammadiyah 1 Pontianak, that is not in accordance with the purpose of learning, this is because in the process of teaching and learning the teacher does not apply the method actively which means the teacher sociology using only teaching methods lectures and methods just answer while the implementation of the learning takes place (3) the application of teaching methods by the teacher of sociology on student activities show students are less understanding and still less active at the time of learning sociology took place. This is evident from the data collected by researchers through interviews, observations and field notes show that teachers have not applied teaching methods.Keyword : Teaching Method Teachers.